Thermal Design Optimization of No Phase Change Shell-and-Tube Heat Exchanger using Particle Swarm Algorithm - Vera Pangni Fahriani; Reza Setiawan; František Hrdlička; Prihadi Setyo Darmanto (University of Muhammadiyah Malang, 2021)
Shell-and-tube heat exchanger is designed to satisfy certain requirements such as heat transfer capability, allowable pressure drop and limitation of size. Beside such requirements, it is important to consider economical point of view to get lowest total cost. In this study, computational program and optimization for thermal design shell-and-tube heat exchanger were built for liquid to liquid with no phase change process in four variables design parameters using Bell-Delaware method. The design variables were tube size, tube length, baffle cut to shell inside diameter ratio and central baffle spacing to shell inside diameter ratio. Particle swarm algorithm was used as optimization method to get lower solution for economical point of view shell-and-tube heat exchanger. The results from two study cases show that particle swarm algorithm got lower total cost from the original design. The total cost decreased 28.84 % in first study case and 52.57 % in second study case from the original design.